Carbon Status in Forests of Nepal: An Overview - Oli, Bishwa Nath; Shrestha, Kumud (Journal of Forest and Livelihood, 2009)
Globally, climate change and mitigation issues have been receiving an increasing attention, and Nepal is no exception. Deforestation is the second single Greenhouse Gas (GHG) source, behind energy production, responsible for about a quarter of anthropogenic GHG emissions. Literature claims that forests have a paramount role in lowering the net GHG emissions to the atmosphere. Forests in Nepal cover nearly 40% of the total land areas and significantly contribute to mitigating the adverse impact of climate change. As no figures are available on biomass and carbon by development and physiographic regions in Nepal, this paper aims at providing information about the total carbon stock in the forests of Nepal. This paper strongly argues for maintaining reliable forestry sector statistics, such as forest cover, growing stock, biomass and carbon in the country. Key words: global warming, carbon stock, carbon emission, deforestation, climate change Full text is available at the ForestAction website Journal of Forest and Livelihood 8(1) February 2009 pp.62-66